Sumoylation and proteasomal activity determine the transactivation properties of the mineralocorticoid receptor - Tirard, Marilyn; Almeida, O. F. X.; Hutzler, P.; Melchior, Frauke; Michaelidis, T. M. (Molecular and cellular endocrinology, 2007)
MR is a hormone-activated transcription factor that carries a strong synergy inhibitory function at its N-terminus. Using this region as bait in a yeast two-hybrid screening, we isolated major components of the sumoylation pathway, including the SUMO-1-conjugating enzyme Ubc9, and SUMO-1 itself. We found that MR interacts with both, Ubc9 and SUMO-1 in mammalian cells, and that the receptor is sumoylated at four acceptor sites which are clustered within its AF-1 domain. We observed that MR can be poly-ubiquitinated and that proteasome activity is essential for MR-activated transcription. Disruption of the SUMO-1 attachment sites abolished MR sumoylation but interfered with neither the poly-ubiquitination of the receptor nor its transactivation potential on MMTV. However, the hormone-activated mutant displayed enhanced synergistic potential on a compound promoter and delayed mobility in the nucleus. FRAP analysis further showed that proteasome inhibition immobilizes a subpopulation of unliganded MR receptors in the nucleus, a phenomenon that is significantly attenuated in the presence of aldosterone. Interestingly, the ability of the hormone to counteract the immobilizing effect of MG132 requires the sumoylation-competent form of MR. Moreover, increasing exogenously SUMO-1 cellular levels resulted in a selective, dose-dependent inhibition of the activity of the sumoylation-deficient MR. This effect was observed only on a synergy-competent promoter, revealing a mode for negative regulation of synergy that might involve sumoylation of factors different from MR. The data suggest that the overall transcriptional activity of MR can be modulated by its sumoylation potential as well as the sumoylation level of MR-interacting proteins, and requires the continuous function of the proteasome.